Designing an Academic Website User Interface Using the Design Thinking Method - Yesa, Caesareano Lafado; Putri, Nabila Annisa; Noer, Dhenok Sagita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
As an educational institution, Telkom University Surabaya (TUS) has academic-related information media that applies to students in the form of academic websites. However, the presentation and management of information regarding academic business processes through the official TUS academic website still has several obstacles. The website has not been managed in a structured manner and is able to provide an easy-to-use experience for users in accessing information. Therefore, this study aims to improve the business process of the TUS academic website to be more informative, structured, and have a modern and user-friendly user interface (UI / UX) design. The research method used is based on a user-centered design approach using design thinking. Design Thinking is a method with an iterative approach that identifies problems and needs of users, with the aim of creating designs that can understand and provide innovative solutions for users. The final result of this research is to create an interface that is easy to understand, responsive, and reflects the characteristics of Telkom University Surabaya (TUS).